1999
DOI: 10.1007/bf02498290
|View full text |Cite
|
Sign up to set email alerts
|

Formation of NH4 + ions in reaction between urea and nitrous acid

Abstract: The interaction of urea and nitrogen oxides produces N 2. This reaction is used in neutralization of nitrogencontaining technological gases and wastes of power, metallurgic, and metal working plants. 1 It is generally accepted 2-4 that urea reacts with nitrous acid according to the equation CO(NH2) 2 + 2 HNO 2 9 2 N 2 + CO 2 +3 H20.However, in acidic solutions urea may also undergo hydrolysis producing CO: and NH4 + ions. 4 Available data on the product composition and kinetics of urea reactions with nitrogen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…Gladyshev et al [18] found that this reaction is of first-order with respect to both N 2 HSO 3 H and HNO 2 . The following rate equation has been suggested by these authors [18]:…”
Section: Effect Of Ammonium Sulfamatementioning
confidence: 97%
See 2 more Smart Citations
“…Gladyshev et al [18] found that this reaction is of first-order with respect to both N 2 HSO 3 H and HNO 2 . The following rate equation has been suggested by these authors [18]:…”
Section: Effect Of Ammonium Sulfamatementioning
confidence: 97%
“…Gladyshev et al [18] stated that HNO 2 first accumulates in solutions containing metal ions and nitric acid and then decomposes to nitrogen oxides. The reactions showing the possible products of decomposition of nitrous acid are presented elsewhere [19,20].…”
Section: Effect Of Ammonium Sulfamatementioning
confidence: 99%
See 1 more Smart Citation
“…64 A kinetic study of the reaction of nitrous acid with sulfamic acid and urea has been reported, and kinetic equations have been derived. 65…”
Section: Ionization and Kinetic Studiesmentioning
confidence: 99%